2023
DOI: 10.3390/buildings13051288
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Response Analysis of a Large-Span Isolated Structure Equipped with TNRB-DSBs and LRBs

Abstract: This study focused on comprehensively analyzing the construction, mechanism, and design theory of the Thick Rubber Bearing–Disk Spring Bearing (TNRB-DSB) system, with the aim of evaluating its isolation effect. Mechanical tests were conducted to examine the dynamic characteristics of large-span isolated structures equipped with TNRB-DSBs, and laminated rubber bearings (LRBs), as well as the dynamic responses of non-isolated structures and large-span horizontal isolated structures equipped with natural rubber b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…As for the relevant parameters of the test device and specimens, since the tests of several support models in our research group were completed together, the test device used was the same as some specimens, and some parameters were referred to another article published by the research group [30]. Vertical parametric variables of compression shear test apparatus are a maximum vertical pressure of 20,000 kN, maximum vertical tension of 6000 kN, maximum vertical displacement stroke of 700 mm, and maximum speed of 3 mm/s.…”
Section: Test Mechanism and Test Specimensmentioning
confidence: 99%
“…As for the relevant parameters of the test device and specimens, since the tests of several support models in our research group were completed together, the test device used was the same as some specimens, and some parameters were referred to another article published by the research group [30]. Vertical parametric variables of compression shear test apparatus are a maximum vertical pressure of 20,000 kN, maximum vertical tension of 6000 kN, maximum vertical displacement stroke of 700 mm, and maximum speed of 3 mm/s.…”
Section: Test Mechanism and Test Specimensmentioning
confidence: 99%
“…In recent years, the base isolation system has been rapidly developed and applied as a technical means to protect the overall safety of structures, from civil buildings, various industrial buildings, and bridges to important infrastructure, including nuclear power plant engineering facilities and structures, and has achieved numerous research results [9][10][11][12][13][14][15]. Pan et al conducted experimental research on the isolation effect of four types of laminated rubber bearings and found that the isolation effect and stability of thick natural rubber bearings and thick high damping rubber bearings were superior to those of thin rubber bearings [16].…”
Section: Introductionmentioning
confidence: 99%